Factors Affecting Nurse's Caring Behavior Towards Chronical Kidney Failure Patients Who Are Taking Hemodialization at PKU Muhammadiyah Gombong Hospital - Luthfiana Dewi; Dadi Santoso; Cahyu Septiwi (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Chronic kidney failure is a public health problem in the world with an incidence of 697.5 million cases. Patients with chronic kidney failure on hemodialysis experience a decreased quality of life good from the aspect physical and psychic. Caring behavior is a dynamic approach to help the patient's healing process which is influenced by several factors as work motivation, knowledge, workload and work environment in carrying out their role as implementers of nursing care. The aim of this research is to identifying factors affecting nurse caring behavior toward chornical kidney failure patients who are taking hemodialization, using quantitative methods through a cross sectional approach by doing crosstab. Research sample is 30 nurses with total sampling model. Instrument in this study using questionnaires. The analysis used is the Kendall Tau. From the research result can be found out that the result is that there is correlation between work motivation toward nurse caring behavior at the hemodialysis room with a significance value (p=0,032), there is not any correlation between knowledge toward nurse caring behavior with a significance value (p=0,054), there is not any correlation between workload toward nurse caring behavior with a significance value (p=0,418) and there is not any correlation between work environment toward nurse caring behavior with a significance value (p=0,228).